ANALISIS YURIDIS PENGAWASAN PERATURAN DAERAH KABUPATEN DAN KOTA TENTANG BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN - WIRA WARDANA (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Budiman Ginting2. Bastari3. Muhd. Yamin Perda (Regional Regulation) on Tax and retribution does not give authority to local government in stipulating the types of new tax and retribution even though local government has bigger opportunity to make Perda on regional tax and retribution. Examination on its regulation becomes very important in the current governmental era. Government’s supervision on Perda is done in order that local government’s policies are not contrary to public interest and to higher regulations. It is also intended to make certain that the Perda has been accordance with the principles of making legal provisions. The result of the research shows that supervision system in making Perda of Districts/Towns is repressive in which Perda on PDRD submitted to the central government can be revoked by the central government when it is contrary to public interest and higher legal provisions. The legal consequence of the violation against the obligations of supervision in Perda on BPHTB is administrative sanction and sanction of delay on the evaluation of Perda draft.Keywords: Regional Tax and Retribution, Supervision on Regional Regulations